STRATEGI KOMUNIKASI PEMASARAN TAMAN BALEKAMBANG DALAM MENARIK WISATAWAN SEBAGAI DESTINASI WISATA BUDAYA DI KOTA SOLO - Putro, Wahyu Ardianto; Suryo Sardjono, Herning (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Indonesia has natural and cultural wealth that can be used as a tourist attraction. One of the interesting cultural tourism destinations in Solo City is Balekambang Park, which is an urban forest tourism and also a cultural heritage area. However, in an effort to attract tourists, the previous promotion of Balekambang Park was still not optimal, especially in the use of digital media. This study aims to describe and analyze the marketing communication strategy used by Balekambang Park to increase its attractiveness as a cultural tourism destination. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study show that the marketing communication strategy carried out by Taman Balekambang is through advertising on Instagram and conventional media, sales promotion with a variety of ticket prices and new facilities, as well as public relations through cooperation with the government, local communities, and influencers. Publicity is done through media articles, and direct marketing is done through special events such as the Ramayana Dance. Although there are obstacles in the implementation of this strategy, there are budget limitations and challenges in community behavior. The strategy implemented is quite effective in attracting tourists who visit and achieve part of their goals. Evaluation and adjustment to this strategy is expected to improve the image and attractiveness of Balekambang Park as a superior cultural tourism destination in the city of Solo. Keywords : Marketing Communication Strategy, Balekambang Park, Tourism, Culture, Promotion.